2005
DOI: 10.1007/s00421-005-0046-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypercapnia on changes in blood pH, plasma lactate and ammonia due to exercise

Abstract: The present study examined the effects of hypercapnia on changes in blood pH, plasma lactate and ammonia due to exhaustive exercise. Six male subjects underwent exercise of increasing intensity until exhaustion: (1) breathing air = MAX (maximal exercise), or (2) under hypercapnia (HC: 21% O 2 , 6% CO 2 ) that had been maintained from 60 min before to 30 min after exercise = HC; and (3) exercise of the same intensity as HC in air = SUB (submaximal exercise). Arterialized blood was drawn from a superficial vein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…the parameter did not reach the sta tistical significance. This result is in accordance with those obtained by researchers studying the effects of hypercapnic gas inhalation (Graham et al [21], Kato et al [19]). In the experiment of the latter, at the end of the exercise per formed in hypercapnia HR was not significantly diffe rent from the same exercise performed without hyper capnia.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…the parameter did not reach the sta tistical significance. This result is in accordance with those obtained by researchers studying the effects of hypercapnic gas inhalation (Graham et al [21], Kato et al [19]). In the experiment of the latter, at the end of the exercise per formed in hypercapnia HR was not significantly diffe rent from the same exercise performed without hyper capnia.…”
Section: Discussionsupporting
confidence: 83%
“…According to their findings, an increase in CO 2 leads to environmental acidosis, thereby inhibiting phosphofructokinase (PKF) and glycolysis (Hollidge-Horvat et al [20], Kato et al [19]). Furthermore, they report that during exercise the blood lactate level under hypercapnia is lower than un der normocapnia (Graham et al [21,22], Kato et al [19]). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can cause an increase in lactate and ammonia in blood (Broomfield and Grunewald, 2012). During maximal exercise, ammonia and lactate levels decrease because of a reduction in blood pH caused by hypercapnia due to respiratory acidosis (Kato et al, 2005). Since ammonia is pH-dependent, breath testing can be linked to protein metabolism and changes of blood pH under exercise (Schubert et al, 2012).…”
Section: Muscle Metabolism and Exercisementioning
confidence: 99%
“…A decrease in blood La concentration during exercise under hypercapnic conditions was previously reported [1][2][3][4], and La threshold (LT) was unchanged by hypercapnia [4]. Further, we reported that plasma Am concentration was reduced at maximal exercise in a 6% inhaled CO 2 condition [5]. However, the changes in Am dynamics during exercise, including Am threshold (AmT), remain unknown since blood samples were drawn following exercise.…”
Section: Introductionmentioning
confidence: 74%